Practices of Preschool Teachers in Promoting Physical Activities During the Covid-19 Pandemic Situation - Sriamporn, Chonticha; Khayankij, Sasilak (An Online Journal of Education, 2024)
The purpose of this research was to study preschool teachers’ practices for promoting physical activities during the Covid-19 pandemic situation in two aspects, comprised of integrating physical activities in daily life and arranging both the teaching environment and atmosphere. The population consisted of 67 preschool teachers in private schools during the academic year 2021. A questionnaire on practices for promoting physical activities during the Covid-19 pandemic situation was used to gather data, then analyzed by using frequency distribution, percentage, means, standard deviation, and content analysis. The research found that preschool teachers promoted physical activities at a high level (M = 4.06). Considerably, all aspects were at a high level: (1) integrating physical activities (M = 3.92), consisting of both classroom activities (M = 4.09) and outdoor activities (M = 3.67); and (2) arranging a teaching environment and atmosphere (M = 4.20), consisting of space and outdoor equipment preparation (M = 4.02) and being a role model (M = 4.31), respectively.